2005
DOI: 10.1002/adv.20051
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of room temperature self‐crosslinking poly(MMA‐co‐BA‐co‐St‐co‐VTES) latex film

Abstract: Self-crosslinking poly(methyl methacrylate-co-n-butyl acrylate-co-styrene-co-vinyltriethoxysilane) latex particles were prepared by seed emulsion polymerization. The presence of Si O Si in the prepared copolymer latex particle was confirmed by FT-IR. The crosslinking degree of the polymer latex particle was investigated by using tetrahydrofuran to swell the dried copolymer films with different vinyltriethoxysilane contents. The thermal properties of the solid films were investigated by using DSC and TGA. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…These results are in agreement with those found by Castelvetro et al [24], who also showed an increase in the modulus above the glass transition with a shift of the drop in E ′ toward higher temperatures [24]. The silanol functionalized latex called also self‐crosslinking emulsion is commercially available and widely used in water‐based paint and adhesive formulations [24, 25].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in agreement with those found by Castelvetro et al [24], who also showed an increase in the modulus above the glass transition with a shift of the drop in E ′ toward higher temperatures [24]. The silanol functionalized latex called also self‐crosslinking emulsion is commercially available and widely used in water‐based paint and adhesive formulations [24, 25].…”
Section: Resultssupporting
confidence: 89%
“…These conditions favor keeping MPS under its hydrolyzed form (silanol) without self‐condensation among silanol groups. The stability of MPS against self‐condensation reaction under neutral condition was supported in previous works [22–25] using 29 Si‐, 13 C‐ and 1 H‐NMR spectroscopy. On the contrary, when polymerization was carried out in the presence of 4 wt% cellulose whiskers, the particle size was found to stabilize around 115 nm as the MPS content was in the range 2–4 wt%.…”
Section: Resultssupporting
confidence: 63%
“…Such systems induce postcross-linking properties at room temperature after hydrolysis of the trialkoxy moiety into silanol groups, followed by condensation leading to ASiAOASiA linkage connecting adjacent polymer chains [14][15][16]. Nonetheless, while this mechanism is approved, all the reported studies agree that the silane content should be higher than 5 wt.%, preferably in the range of 10-12%, in order to promote the probability of (coupling) contact among the hydrolysed silanol to ensure efficient cross-linking.…”
Section: Frequency Response Of Neat Matrix During Linear Behaviourmentioning
confidence: 99%
“…Since the 1970s several scientists [117][118][119][120][121][122][123] have investigated the behaviors of crosslinked PMMA. Crosslinked PMMA is used in a variety of commercial materials such as membranes [124], dental fi llings [125], dentures, latex coatings [126], computer-to-sensor data transmission links [127], composites [128], optically clear sheeting, limb prostheses, bathtubs, bathroom sinks and shower surrounds, etc., where crosslinking plays a vital role in both processing and ultimate properties.…”
Section: Crosslinking Monomer(s)mentioning
confidence: 99%